Clay Mineral–Hydrophobic Organic Compound Interactions in Miniaturized Adsorption Experiments: Exemplary Studies With Bentonites and Hexachlorobenzene - Böhm, Leonard; Grancic, Peter; Butzke, Lilli P.; Kaufhold, Stephan; Siemens, Jan; Tunega, Daniel; Gerzabek, Martin H.; Justus Liebig University Giessen (My University, 2024)
Background: Hydrophobic organic compounds (HOCs) are ubiquitous in the environment. Especially halogenated HOCs can pose a major threat to human and environmental health. They show high affinity toward organic matter (OM), and adsorption processes are extensively investigated. Contrary, adsorption to minerals is often considered negligible, and knowledge on HOC interactions with clay minerals (CM) is still scarce. Aims: We aimed to apply an optimized method for the straightforward and sensitive quantification of HOC–CM interactions in miniaturized systems to quantify hexachlorobenzene (HCB) adsorption to native bentonites and to evaluate the influence of different mineral characteristics on adsorption. Methods: HOC–CM interactions were studied in miniaturized batch adsorption experiments with HCB as HOC representative and 21 native bentonites as CM phases. Additionally, five of the bentonites were used as sorbents after wet size fractionation (<2 µm) and homoionic cation exchange (Ca2+). Linear adsorption isotherms and solid–liquid distribution coefficients Kd were calculated after HCB analysis by solid-phase microextraction (SPME) coupled to GC–MS. Results: HCB adsorption to selected native bentonites showed a large variation over several orders of magnitude (log Kd 1.8–4.1). Size-fractionation and Ca2+-modification tended to slightly decrease the Kd values compared to the five corresponding native bentonites (log Kd: 1.9–3.8 vs. log Kd: 2.0–4.1). Most promising parameters for explaining adsorption strength by different CM characteristics were layer charge density (LCD) and cation exchange capacity (CEC). However, no single factor could be attributed to explain the observed variability of adsorption. The miniaturized batch adsorption method reduces the required amounts of purified CM and toxic chemicals while providing excellent sensitivity and reproducibility. Conclusions: HOC adsorption to native, smectite-rich bentonites is mostly moderate but can be as high as adsorption to pure OM phases for some bentonites. The variation in adsorption appears to be controlled by a combination of several factors that might include additional factors not previously considered, especially for the bentonites with the strongest adsorption of HCB.
Keywords: ddc:630